1993
DOI: 10.20870/oeno-one.1993.27.2.1176
|View full text |Cite
|
Sign up to set email alerts
|

Relations entre le développement défectueux des ovaires et l'involution des ovules chez <em>Vitis vinifera</em> L. var. Chardonnay

Abstract: <p style="text-align: justify;">Chez <em>Vitis vinifera</em> L. var. Chardonnay, le développement normal des ovules est de type <em>Polygonum</em>, mais les antipodes sont éphémères. Un grand nombre d'ovules ne peuvent suivre une ontogénie normale et involuent plus ou moins précocement. Plusieurs symptômes sont indubitablement des signes annonciateurs de l'arrêt du développement et d'une involution conduisant à la dégénérescence des ovules.</p><p style="text-align: justif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Another factor affecting fertilisation and fruitset in grapevines is the functionality of the embryo sac, including the synergid cells, which are demonstrated to have a crucial role in attracting the pollen tube (Fougère‐Rifot et al . , Ebadi ). Various aberrations of ovule development can cause poor pollen tube growth and fruitset in grapevines (Fougère‐Rifot et al .…”
Section: Resultsmentioning
confidence: 99%
“…Another factor affecting fertilisation and fruitset in grapevines is the functionality of the embryo sac, including the synergid cells, which are demonstrated to have a crucial role in attracting the pollen tube (Fougère‐Rifot et al . , Ebadi ). Various aberrations of ovule development can cause poor pollen tube growth and fruitset in grapevines (Fougère‐Rifot et al .…”
Section: Resultsmentioning
confidence: 99%
“…setting. Fougère-Rifot et al (1993) have concluded that poor fruit-set may be due to aberrant ovule development, either during meiosis, when ovule abortion is frequent, or later when pollination and fertilisation might occur but fail because of cellular defects (involution) within the ovule. In Shiraz the trend for berry number and 'sinker'-seed number to show similar trends in their response to the applied treatments was similar but less pronounced than in Chardonnay; this is not surprising because this cultivar showed a lesser overall response to the low temperature treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The situation concerning the state of tannin vacuoles cannot be compared because tannin evolution seems to be determined at a stage preceding the observations in the present study. Fougère-Rifot et al (1993) also stated that "in Chardonnay, at the time of pollination, we found only rarely an ovary with more than one healthy ovule". In the present experiment there were about 50% of all Control ovaries with four normal ovules.…”
mentioning
confidence: 83%